2022
DOI: 10.3390/biomedicines10081860
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Progesterone Receptor B in MCF-7 Cells Enable Radical Anti-Tumoral and Anti-Estrogenic Effect of Progestin

Abstract: The widely reported conflicting effects of progestin on breast cancer suggest that the progesterone receptor (PR) has dual functions depending on the cellular context. Cell models that enable PR to fully express anti-tumoral properties are valuable for the understanding of molecular determinant(s) of the anti-tumoral property. This study evaluated whether the expression of high levels of PR in MCF-7 cells enabled a strong anti-tumoral response to progestin. MCF-7 cells were engineered to overexpress PRB by sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The MCF-7 cell line is sensitive to progestins: P 4 was shown to inhibit the proliferation of these cells with an IC 50 value of 6.5 ± 0.2 μM [ 42 ]. The anticancer action of progestins is known to be realized via the membrane and nuclear progesterone receptors (PR) [ 43 ]. Since all the drugs tested downregulated the ANT1 expression in MCF-7, it can be assumed that ANT1 downregulation in PR-positive cells can lead to cell death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCF-7 cell line is sensitive to progestins: P 4 was shown to inhibit the proliferation of these cells with an IC 50 value of 6.5 ± 0.2 μM [ 42 ]. The anticancer action of progestins is known to be realized via the membrane and nuclear progesterone receptors (PR) [ 43 ]. Since all the drugs tested downregulated the ANT1 expression in MCF-7, it can be assumed that ANT1 downregulation in PR-positive cells can lead to cell death.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the participation of ANT1 in the regulation of cell viability by steroid hormones and DCF, we examined their effect on the viability and ANT1 expression in cancerous cell lines sensitive to steroid hormones. As is known, all the cell lines, HeLa [ 46 ], MCF-7 [ 43 ], Hep-2 [ 47 ], and K-562 [ 48 ], contain steroid hormone receptors. It is known that PR and GR are expressed in the lung fibroblasts [ 49 ]; however, information about the expression of PR or GR in the Wi-38 cell line is not available.…”
Section: Discussionmentioning
confidence: 99%
“…The surface receptors with high expression in the mentioned cell lines were also evaluated using molecular docking. EGFR (PDB ID: 5WB7) 21) was chosen for SPC-A-1 22) , estrogen receptor (PDB ID: 3OS8) was chosen for SK-LU-1 cells 23) , CD47 (PDB ID: 2JJS) 24) was chosen for 95D 25) , progesterone receptor (PDB ID: 1A28) was chosen for MCF7 26) , folate receptor (PDB ID: 4LRH) was chosen for Hs 578Bst 27) , CD44 (PDB ID: 4PZ3) 28) was chosen for Hs 319.T 27) , HER2 (PDB ID: 1N8Z) 29) was chosen UACC-3133 30) , CD155 (PDB ID: 3URO) 31) was chosen for CL40 32) , CXCR4 (PDB ID: 3ODU) 33) was selected for SW1417 34) , CD97 (PDB ID: 7DO4) 35) was selected for LS1034 36) , and endothelin receptor (PDB ID: 5X93) 37) was selected for SW480 38) . The chemical activities of isokaempferide were estimated against these enzymes and proteins.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…However, progesterone-induced replicative senescence through β-gal activity, particularly PRA presence, but to a much lesser extent by PRB [204]. Bajalovic et al (2022) observed the opposite effect after treating breast cancer MCF-7 cells in the synthetic form of progesterone-progestin (R5020). These synthetic hormones induced replicative senescence in MCF-7, expressing high levels of PRB.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…R5020 in MCF-7 caused a reduction in CDK2 and CDK4 and decreased in S phase cells. Progestin in MCF-7PRB cells activated the NF-κB pathway by phosphorylating IκBα and p65 pathways, leading to increased expression of SASP, such as IL-1a, IL-1b, and IL-8 [205]. Another synthetic form of progesterone is megestrol acetate.…”
Section: Hormonal Therapymentioning
confidence: 99%